Find the sum of all p , q , s such that
2 m . p 2 + 1 = q s
and p , q , s are odd primes and m is not divisible by 4.
Clarification :
For every such triple, add the values of p , q and s to obtain the answer.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
u didn't explain why p does not divide q − 1 .
Here's the reason.
( q − 1 ) ( q s − 1 + q s − 2 + . . . . + 1 ) = p 2 2 m Since, ( q s − 1 + q s − 2 + . . . . + 1 ) is odd and greater than 1 , it is must and should be divisible by p .
Then, either p ∣ q − 1 or p 2 ∣ ( q s − 1 + q s − 2 + . . . . + 1 ) . The latter one can be solved easily, let's check the first one.
If p ∣ q − 1 , let us observe what happens.
Since, q s − 1 + q s − 2 + . . . . + 1 is odd, it forces that q s − 1 + q s − 2 + . . . . + 1 = p and 2 m ∣ q − 1 . So, q − 1 = 2 m p .
So, q = 2 m p + 1 . But s > 2 , so, q s > q 2 = 2 2 m p 2 + 2 m + 1 p + 1 > 2 m p 2 + 1 , a contradiction. So, p ∣ q − 1 .
So, the latter one follows.
Since the solution is very big, I willl divide it into two parts.
To start with, obviously q s ≡ 1 ( m o d 2 m ) .Let v be the order of q modulo 2.Then v must divide s and φ ( 2 m ) = 2 m − 1 .But s is odd, so v must be 1.So now we have that q ≡ 1 ( m o d 2 m ) .We let q = 2 m . k + 1 .But since q-1 divides q s − 1 , we have that 2 m . k ∣ 2 m . p 2 .That means that k is 1,p or p 2
Case 1:k=1.
In this case q = 2 m + 1 , so q is a Fermat prime.That means that m must be a power of 2.But m is not divisible by 4, so m is 1 or 2.This gives us two equations which we will handle in the next part, namely 2 p 2 + 1 = 3 s and 4 p 2 + 1 = 5 s .
Case 2:k=p
2 m . p 2 + 1 = ( 2 m . p + 1 ) s .
But expanding (using the Binomial theorem),we get that p must divide s, so p is equal to s.But then 2 m p . p p > 2 m . p 2 and these are the first terms of the RHS and LHS respectively.So RHS>LHS, a contradiction.
Case 3:k=p^2
Here we would have that s=1, clearly not possible, since s is a prime number.
But that is just the first part, since we have yet to solve the equations from Case 1. But they can be solved using unique factorization in Z ( i ) and Z ( − 2 ) .
m = 0 m a k e s L H S a s e v e n . B u t R H S i s A L W A Y S o d d . ∴ m = 0 . T o s t a r t w i t h t r i a l m = 1 , 2 , a n d p = 1 . F i n d o u t t h e i n t e g e r w e g e t f r o m 2 m q s − 1 w h e r e q = 3 , 5 , 7 , 1 1 , f o r e a c h o f s = 3 , 5 , 7 . I f w e g e t a n i n t e g e r i t i s p f o r t h o s e v a l u e s o f o t h e r v a r i a b l e s . W i t h i n t h e r a g e t h e r e w a s o n l y O N E s o l u t i o n . O n l y i n t e g e r a n s w e r w a s 1 1 . S o o n e s o l u t i o n i s ( p , q , s ) = ( 1 1 , 3 , 5 ) T r i e d o t h e r b i g g e r p r i m e s , a n d m = 3 , 5 , 6 . n o n e g a v e a n i n t e g e r . S o p + q + s = 1 1 + 3 + 5 = 1 9 .
Can any one give a simple proof that there is only one solution, or this is the only solution? Thanks.
Problem Loading...
Note Loading...
Set Loading...
p ∣ ( q s − 1 ) .Note that p cannot divide q − 1 as it is even.
So, p must divide q s − 1 + q s − 2 + . . . 1 .
Now, q s − 1 + . . . + 1 is purely odd.
So we have, 2 m = q − 1 or, q = 2 m + 1
Now, m = 2 t So, t = 0 or 1
So, we have to equations-(a) 2 p 2 = 3 s − 1 and (b) 4 p 2 = 5 s − 1
Note that (b) has no solutions and (a) only has ( 1 1 , 3 , 5 ) has solution.